Clinical and genetic characteristics of patients with Doose syndrome. Issue 3 (23rd July 2020) - Hinokuma, Nodoka; Nakashima, Mitsuko; Asai, Hideyuki; Nakamura, Kazuyuki; Akaboshi, Shinjiro; Fukuoka, Masataka; Togawa, Masami; Oana, Shingo; Ohno, Koyo; Kasai, Mariko; Ogawa, Chikako; Yamamoto, Kazuna; et al.
Abstract: Objective: To elucidate the genetic background and genotype‐phenotype correlations for epilepsy with myoclonic‐atonic seizures, also known as myoclonic‐astatic epilepsy (MAE) or Doose syndrome. Methods: We collected clinical information and blood samples from 29 patients with MAE. We performed whole‐exome sequencing for all except one MAE case in whom custom capture sequencing identified a variant. Results: We newly identified four variants: SLC6A1 and HNRNPU missense variants and microdeletions at 2q24.2 involving SCN1A and Xp22.31 involving STS . Febrile seizures preceded epileptic or afebrile seizures in four patients, of which two patients had gene variants. Myoclonic‐atonic seizures occurred at onset in four patients, of which two had variants, and during the course of disease in three patients. Variants were more commonly identified in patients with a developmental delay or intellectual disability (DD/ID), but genetic status was not associated with the severity of DD/ID. Attention‐deficit/hyperactivity disorder and autistic spectrum disorder were less frequently observed in patients with variants than in those with unknown etiology. Significance: MAE patients had genetic heterogeneity, and HNRNPU and STS emerged as possible candidate causative genes. Febrile seizures prior to epileptic seizures and myoclonic‐atonic seizure at onset indicate a genetic predisposition to MAE. Comorbid conditions were not related to genetic predisposition to MAE.